Theological Aesthetics and Everyday Neoliberalism - Fritz, Peter (TEOLITERARIA - Revista de Literaturas e Teologias, 2017)
Theological aesthetics in the present must turn toward everyday life, especially because of neoliberal capitalism’s comprehensive deformation of the everyday. Karl Rahner’s theology, with its emphasis on Jesus Christ’s (re)configuration of everyday human life, proves dually advantageous for turning theological aesthetics toward the everyday and generating Catholic, theological-aesthetic discursive resistance to neoliberalism’s pernicious everyday aesthetic. This article’s first part explicates what constitutes a Rahnerian theological aesthetic: the embeddedness of Jesus Christ in everyday human life, which is “aesthetic” in its embodiedness. Part two switches focus to neoliberal capitalism, providing a brief account of how it distinctively shapes everyday human life, especially with regard to fragmentation of the self, tacit support for systemic cruelty toward others, and somatic manipulation. Part three suggests how Rahner’s theological aesthetic, with its robust account of embodied aesthesis as expressive of deep spiritual freedom shaped by Christic transformation, proves resistant to everyday neoliberalism, which is an aesthetic shaped by marketization of the human person and punitive behavior toward people deemed “market failures” (who in Christian parlance we would call “the least of these,” Mt 25:45).